Public’s Perception and Preference Towards Halal Tourism - Maulani, Aghnia Nur; Ayuningtyas, Rosida Dwi; Alfie, Atieq Amjadallah (EkBis: Jurnal Ekonomi dan Bisnis, 2021)
Halal tourism is a sector that has an important role in the economic development. For that, the main purpose of this study is to explore the perceptions and preferences of public towards halal tourism. It also aims to describe the level of importance performance of the halal tourism indicators in Semarang City and Kendal Regency. The design of this study was descriptive with quantitative approach. Data collection technique in this paper are randomly distributing questionnaires to 400 respondents. The halal tourism dimension is adapted from indicators applied by the Indonesian Muslim Travel Index. Then, the data analyzed by Gap Analysis and Importance Performance Analysis. The Result obtained that there are some indicators have low performance where as the level of influence is high, some indicators with level of influence followed by good performance, some indicators that have low level of influence and the performance is not good, and the indicators that the influence level is low but its performance is good